Distance Learning in Highereducational System of Georgiaduring COVID-19 Pandemic Situationand Satisfaction of Students - Gakharia, Tatia; Besiashvili, Nino; Sulashvili, Nodar (Caucasus Journal of Health Sciences and Public Health, 2020)
According to the pandemic situation, face-to-face education system was cancelled countrywide and drastically increased online learning platforms. Because of emergency state countrywide according to safety recommendations,all students in Georgia and international students were able to complete their course without ever setting foot on university. Distance learning model gave ability to work remotely and decrease the disruption of the educational system. Researchers and educators are unwarranted how the education in emergencies differ from students experiences and expectations in traditional on-site environments . While these treats may be unsure, there is smallstudy to precisely ascertain the benefits and difficulties of online teaching, in particularly when contrasted to face-to-face learning. Asses knowledge about the educational process changes and outcomes of online instruction during COVID-19 in Georgia in comparison to face-to-face environments will help educators and researchers develop more informed choice about future distant learningcourses andfixes idea of online platform implementation in educational curriculum.